FIRST STUDY ON THE USAGE OF OVAPRIM FOR THE INDUCED SPAWNING OF COMMON CARP (CYPRINUS CARPIO) IN BASRAH - IRAQ - Almukhtar, MUSTAF A.; ALNOOR, SAJD S.; FADAGH, M. S.; ABDULKAREEM, TAQI (Iraqi Journal of Aquaculture, 2022)
The synthetic hormonal product Ovaprime was used for the induced spawning of Cyprinus carpio , in comparson with the Pituitary gland extract. The study was done in Basrah univ. Marine Sience Center freshwater fish hatchery. The Ovaprime is an Analog of Gonadotropine releasing hormone of salmon (sGnRHa) as well as Domperidone as Dopamine Antagonist. The first fish group of C.carpio was injected with 0.5 ml of Ovaprime in one dose , while the second ( control) group was injected with PG extract in two dose ( 0.3mg/kg as a first & 3.0 mg/Kg as a second dose). The results showed that the usage of Ovaprime gives better results than PG extract in the performing parameters of induced spawning. Average Ova weight provided by hand stripping was higher in Ovaprime treatment. The average ova weight per body weight was also higher in Ovaprime (11.97%) compaired with 7.245% for PG, but these results were not statisticaly significant . With Ovaprime all the fishes had free flowing Ova while half of the fishes had free flowing ova in PG injected fishes. Fertilization rate was higher (95%) with Ovaprime, and this was highly significant differences from PG. Hatching rate was increased by Ovaprime to reach 93.75% while it was 83.75% for PG,it was also significant differences. In addition to that it was seen that the usage of Ovaprime is more practical in the hatchery management work..also It was found that Ovaprime is cheapest than the usage of PG extraction during the study period.